2011
DOI: 10.5007/2175-7925.2010v23n1p27
|View full text |Cite
|
Sign up to set email alerts
|

<b>Armazenamento criogênico de sementes de pinhão manso (Jatropha curcas L.) Euphorbiaceae</b><br>doi: 10.5007/2175-7925.2010v23n1p27

Abstract: ResumoO presente trabalho teve como objetivo avaliar a qualidade fisiológica de sementes de pinhão manso armazenadas em nitrogênio líquido, a temperatura de -196ºC e no vapor de nitrogênio a -170ºC, por períodos de 0, 30, 60 e 90 dias. As sementes foram armazenadas em botijões criogênicos, que mantêm o nitrogênio nas fases líquida e vapor. Os parâmetros avaliados foram germinação e vigor obtidos no 14º dia depois da semeadura.O delineamento estatístico foi inteiramente casualizado, empregando-se duas temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…), which facilities the formation of intracellular ice crystals that cause ruptures in the endomembrane system and compromise cellular compartmentalization (Goldfarb et al . ; Wesley‐Smith et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), which facilities the formation of intracellular ice crystals that cause ruptures in the endomembrane system and compromise cellular compartmentalization (Goldfarb et al . ; Wesley‐Smith et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Astronium urundeuva (urunday) seeds maintained their viability when cryopreserved with 6% m c water content (Medeiros et al, 1992). Similarly, Jatropha curcas L. (Barbados nut) seeds maintained their vigour index when stored in liquid nitrogen or in vapour (Goldfarb et al, 2010) and their high viability when cryopreserved with 8% m c water content (Silva et al, 2011). Tabebuia chrysotricha (golden trumpet tree) seeds showed higher germination when cryopreserved with 4% m c water content (Tresena et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, in a low-temperature germplasm bank, not only the cryopreservation process but also the thawing method must be considered, since the faster the thawing of seeds, the better is the preservation of their physiological characteristics. This procedure may prevent the ice crystals within the cell, which would lead to destruction of the membrane and consequently cause cell death (Goldfarb et al, 2010). Kholina & Voronkova (2008) using 103 species and Voronkova & Kholina (2010) using 11 species endemic to eastern Russia found that cryostored seeds subjected to slow thawing for 2 h, under laboratory environmental conditions (20−25 °C), had no loss or physiological damage.…”
Section: Dimethyl Sulfoxide Use In Cryopreservationmentioning
confidence: 99%
“…The ex situ preservation shows some advantages compared to in situ, such as reduced need for space, lower expenses and labor costs, easier germplasm exchange, and reduced genetic erosion (Engelmann, 1991). Seed preservation is the easiest, most common and efficient means of ex situ preservation, since the seeds ensure genetic variability, are easily collected, and occupy small spaces (Li & Pritchard, 2009;Goldfarb et al, 2010;Pence, 2010).…”
Section: Introductionmentioning
confidence: 99%